Analysis of Added Value and Business Feasibility of Sago Tempe Chips Home Industry - Andini Afifah; Abubakar Abubakar; Muhamad Rom Ali Fikri (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This study aims to examine the added value and feasibility of the home industry producing tempeh sago chips in Bekasi. Methodology: The research employs both quantitative and qualitative descriptive methods to analyze the data. Results: The results indicate that the main reason for establishing the home industry of tempeh sago chips in Bekasi is to increase household income and create job opportunities for local residents. The added value obtained is an average of IDR 8,781.51/kg with an added value ratio of 19%, indicating a moderate level as it falls between 15% and 40%. The R/C Ratio is 1.53, where an R/C Ratio ≥ 1 is considered favorable. The Break-Even Point (BEP) for revenue is IDR 306,105.84, the BEP for production is 4.91 kg, and the BEP for price is IDR 40,817/kg. Findings: The study finds that the home industry of tempeh sago chips in Bekasi is viable and profitable, despite facing challenges such as the lack of bookkeeping practices. Novelty: This research provides new insights into the economic value addition and business feasibility of tempeh sago chips, highlighting the importance of proper financial management. Originality: The study presents a detailed analysis of the feasibility and value addition of tempeh sago chips, contributing to the understanding of small-scale food industries in Bekasi. Conclusions: The home industry of tempeh sago chips in Bekasi is feasible and profitable, making it a sustainable business venture. Type of Paper: Empirical Research Article